A Note on the Managerial Relevance of Interdependence - Johansson, J. K. (Journal of International Business Studies, 1982)
The concept of interdependence between countries is analyzed from the viewpoint of a profit-making firm. The author shows how the level of interdependence becomes important for risk-avoiding, international sourcing and marketing decisions. By implication, the manager's most useful option is one which includes not only varying degrees of but also positive and negative types of interdependence.